Pengaruh Neuroaccounting terhadap Pencegahan Risiko Fraud, dengan Kecerdasan Spiritual sebagai Variabel Intervening - Ersa, Andina; Soenaria, Syaiful Rahman; A, Gia Kardina Prima (Ekonomis: Journal of Economics and Business, 2026)
This study aims to analyze the influence of neuroaccounting on the cognitive and affective aspects of fraud risk prevention, both directly and through spiritual intelligence as an intervening variable. The causality method was used to analyze the cause-and-effect relationship between variables, focusing on the influence of neuroaccounting (cognitive and affective aspects) and spiritual intelligence on fraud risk prevention. The results of this study indicate that although affective neuroaccounting has a positive influence on fraud risk prevention through spiritual intelligence, cognitive neuroaccounting does not have a significant indirect effect. Surprisingly, both cognitive and affective neuroaccounting have a negative direct impact on fraud risk prevention. This suggests that relying solely on cognitive or affective approaches without a strong ethical foundation may be ineffective in preventing fraud. This study highlights the importance of spiritual intelligence in encouraging ethical behavior to mitigate fraud. Therefore, the results of this study can assist companies in employee recruitment, making them more selective, and in job-specific assessments that can help detect an individual's propensity to commit fraud.